Crítica de poder estadunidense em filmes de guerra - Braga, Wendel Nascimento (2021)
Hollywood cinema is part of the context of the so-called cultural industry and has always stood out for its dominance of the film market. The consequence is that he takes advantage of this condition to insert ideologies of cultural superiority in relation to thecultures of other peoples in film narratives, often resulting in the spread of racism and prejudice of various orders. Thus, the objective of this research was to demonstrate this practice of using the language of cinema, in the War Films genre, as a phenomenon of diffusion of the ideology of American cultural power and an instrument of social differentiation present in Hollywood cinematographic productions of this type. The analyzes were developed in order to identify how the circumstances in which the brands appear along the narratives investigated in the chosen films occur. In this way, it is possible to extract evidence that confirms the intention with which the work was carried out, evidencing a promotion of the image of superiority in the US, as well as enabling the criticism of this strategy of diffusion of elements that somehow highlight the belief in superiority cultural.